Quality Improvement: Changing Patterns of Antibiotic Prophylaxis for Surgical Abortions [23]. (May 2016) - Nguyen, Olivia T.; Shorter, Jade M.; Calfee, Alexa L.; Creinin, Mitchell D.; Hou, Melody Y.
Abstract : INTRODUCTION: Patients at our institution having an abortion in the operating room are routinely prescribed prophylactic antibiotics to use the night before the procedure. After a quality assurance assessment from 4/2012–6/2013 showed poor documentation and adherence to prescribed antibiotics, we altered our procedures by preferentially using the clinic pharmacy for prescriptions and implementing a standardized preoperative template that included assessment of antibiotic adherence. METHODS: Using clinic schedules, we identified women who had abortions in the operating room from 4/2012–6/2013 and 4/2014–6/2015. We examined electronic medical records to confirm the abortion occurred and obtained data including demographics, prophylactic antibiotic documentation, and patient adherence. We compared data from the two time periods to assess the impact of the interventions on antibiotic provision and documentation. RESULTS: We identified 252 and 445 patients who had abortions during the two time periods, respectively. One patient in the latter group was excluded because she refused antibiotics. Patient characteristics included mean age of 28 years, 34% white, 24% black, and 72% Medicaid-insured. Antibiotic adherence documentation improved from 69.4% (175/252) to 99.1% (440/444 P <.001). Among patients with documentation, antibiotic use the night before the procedure increased from 78.3% (137/175) to 90.0% (396/440, P <.001). Antibiotic administration in the pre-operative area for nonadherent patients increased from 84.4% (27/32) to 97.7% (42/43, P =.036). The proportion of patients who received no antibiotics decreased from 2.4% (6/252) to 0.5% (2/444, P =.009). CONCLUSION/IMPLICATIONS: Using a standardized preoperative template and clinic pharmacy improves provision of prophylactic antibiotics for patients undergoing abortion in the operating room.